Conflict of Laws Without a Code: A Case Note on a Recent Norwegian Supreme Court Judgment Illustrating Contemporary and Historical Methodological Challenges in a European Non-EU State - Sinander, Erik (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This case note deals with a recent Norwegian Supreme Court judgment on the law applicable to non-contractual obligations arising out of wrongful ship engines built in Germany in the early 2000’s. Although the Rome II Regulation (Regulation 864/2007) is neither binding on Norway nor in force within the EU at the time, the Supreme Court paralleled its conclusions on  nalogous interpretations of the regulation, ruling out the application of Norwegian law. The case illustrates the strong impact that EU private international law thinking has also beyond the EU. In the principal and eternal conflict of laws issue of relying on either the law where the injury takes place (lex loci delicti commissi) or the place where the damage occurs (lex loci damni), the EU regulation marked a turn for most EU member States by prioritizing lex loci damni. In the Norwegian case, the EU solution seems to have influenced the Supreme Court’s conclusion. It is remarkable that no analogies are being drawn to private international law instruments that actually are binding on Norway, such as the 1973 Hague Convention on the Law Applicable to Products Liability, where the default rule is lex loci delicti commissi.
Keywords: Private International Law; Non-Contractual Obligations; Rome II Regulation; Norway; Products Liability